Tong-Xie-Yao-Fang Regulates 5-HT Level in Diarrhea Predominant Irritable Bowel Syndrome Through Gut Microbiota Modulation - Li, Junchen; Cui, Huantian; Cai, Yuzi; Lin, Jin; Song, Xin; Zhou, Zijun; Xiong, Wantao; Zhou, Huifang; Bian, Yuhong; Wang, Li (Frontiers in Pharmacology, 2018)
Tong-Xie-Yao-Fang(TXYF) has been widely used for the treatment of diarrhea-predominant irritable bowel syndrome(IBS-D) in traditional Chinese medicine, However, the mechanism of TXYF action in the treatment of IBS-D remains to be fully understood. Recent reports have shown gut microbiota Clustridium can induce 5-HT production of intestinal pheochromocytes that then contribute to IBS. Due to TXYF’s wide use in clinical treatment of IBS-D and the close relationship between gut microbiota and IBS-D, we hypothesize TXYF could modulate gut microbiota and regulate 5-HT levels in gut to treat IBS-D. In this study, variation analysis of 16s rRNA was conducted to determine the distributive changes of gut microbiota in IBS-D model rats after TXYF treatment. Moreover, we investigated whether TXYF could affect 5-HT levels in IBS-D model rats. In addition, fecal transplantation was used to confirm TXYF allieviates IBS-D through modulating gut microbiota and reducing 5-HT production in intestinal pheochromocytes. Result demonstrated TXYF treatment can ameliorate IBS-D and regulate 5-HT levels in intestinal pheochromocytes. TXYF treatment also affected diversity of gut microbiota and altered the relative abundance of Clostridium sensu stricto1 in gut flora populations. Moreover, fecal transplantation from TXYF-treated rats can relieve IBS-D and regulate 5-HT gut levels. In conclusion, the present study demonstrates TXYF treatment favorably affects microbiota levels in gut flora communities and can be used for the treatment of IBS-D. As well, TXYF diminishes 5-HT levels in gut through regulating gut microbiota species.